2010
DOI: 10.1590/s1984-29612010000400008
|View full text |Cite
|
Sign up to set email alerts
|

Sandflies (Psychodidae: Phlebotominae) survey in an urban transmission area of visceral leishmaniasis, Northeastern Brazil

Abstract: Visceral leishmaniasis (VL) is a major public health challenge in Brazil, especially in states where it is endemic. The aim of this study was to investigate the relationship of sand fly population density with environmental variables (temperature, rainfall and relative humidity) in urban areas of the city of Mossoró, Rio Grande do Norte, Northeastern Brazil. Sand flies were captured with Center Disease Control (CDC) traps installed monthly in the intra and peridomicile of three houses. Data analysis was based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
(38 reference statements)
0
4
0
11
Order By: Relevance
“…Estudos realizados com imagens de média resolução espacial e métodos tradicionais de classificação foram capazes de identificar alguns elementos relativos à cobertura vegetal, ao uso do solo e a padrões de ocupação urbana associados ao risco de LV 25,30,35,36,37 . Contudo, a aplicação da classificação orientada a objeto às imagens de média resolução espacial pode apresentar vantagens potenciais em relação a esses métodos, como uma maior reprodutibilidade, flexibilidade e utilização de informações contextuais para além das espectrais 9 .…”
Section: Campo Térmico Da Superfície Do Solounclassified
“…Estudos realizados com imagens de média resolução espacial e métodos tradicionais de classificação foram capazes de identificar alguns elementos relativos à cobertura vegetal, ao uso do solo e a padrões de ocupação urbana associados ao risco de LV 25,30,35,36,37 . Contudo, a aplicação da classificação orientada a objeto às imagens de média resolução espacial pode apresentar vantagens potenciais em relação a esses métodos, como uma maior reprodutibilidade, flexibilidade e utilização de informações contextuais para além das espectrais 9 .…”
Section: Campo Térmico Da Superfície Do Solounclassified
“…In the Americas, the transmission cycle is characterized by the bite of a female sand fl y, Lutzomyia longipalpis, infected with Leishmania infantum chagasi (1) .…”
mentioning
confidence: 99%
“…Previous studies performed in Mossoró reported the presence of the VL vector in different areas of the city throughout the year 7 . The riverside areas in this study included favorable conditions for sand fl ies and dogs infected with L. infantum; thus, we assumed that this population is vulnerable to VL, as confi rmed by previous surveys 20, 21 .…”
Section: Factors Associated With Transmission and Preventionmentioning
confidence: 97%
“…Previous studies have demonstrated the relationship between environmental variables and the density of vectors 7,8 ; in particular, areas that fl ood during the rainy season due to their proximity to rivers are more vulnerable to VL because they have a higher insect density, particularly around homes 9 .…”
Section: Introductionmentioning
confidence: 99%